1983
DOI: 10.1007/bf01765907
|View full text |Cite
|
Sign up to set email alerts
|

Bamus volcano, Papua New Guinea: Dormant neighbour of Ulawun, and magnesian-andesite locality

Abstract: ZusammenfassungBamus und Ulawun iiberragen mit mehr als 400 m alle anderen Hauptvulkane im 1000 km langen Bismarek-Vulkanbogen. Beide Kegel liegen sieh unmittelbar gegenfiber und sind teflweise miteinander verbunden. Die enge Nachbarsehaft, die Nhnlichkeit in der Morpholegie und die gleiehe Entfemung (70---160 km) yen der New Britain Benioff-Zone k6nnen Anzeiehen dafiir sein, dab Bamus und Ulawun in Beziehung miteinanderstehen oder letztendlieh die gleiche eruptive Gesehiehte haben. Aber es gibt wiehtige Unter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This finding is significant because it represents the only active volcano in which a boninitic suite (i.e., eruptives derived from a parental boninite liquid) has been discovered and is the first boninitic suite reported from a normal arc segment. Johnson et al [1983] reported a single high‐Ca boninite lava flow on Bamus Volcano in the New Britain Arc, apparently unrelated to other eruptives at this location. The appearance of high‐Ca boninitic volcanism within a mature intra‐oceanic island arc also implies that extraordinary tectonic settings are unnecessary to explain the genesis of some boninites.…”
Section: Introductionmentioning
confidence: 82%
“…This finding is significant because it represents the only active volcano in which a boninitic suite (i.e., eruptives derived from a parental boninite liquid) has been discovered and is the first boninitic suite reported from a normal arc segment. Johnson et al [1983] reported a single high‐Ca boninite lava flow on Bamus Volcano in the New Britain Arc, apparently unrelated to other eruptives at this location. The appearance of high‐Ca boninitic volcanism within a mature intra‐oceanic island arc also implies that extraordinary tectonic settings are unnecessary to explain the genesis of some boninites.…”
Section: Introductionmentioning
confidence: 82%
“…Ulawun is a 2334 m‐high stratovolcano with a history of frequent and violent strombolian eruptions in recent times [ Venzke et al , 2002–2011]. Eruptions since the 1970s have been of greater intensity than the preceding 100 years and have involved lava flows and major pyroclastic avalanches [ Melson et al , 1972; Johnson et al , 1983]. These avalanches have been linked to instability‐driven edifice collapse, which is considered the most significant hazard associated with Ulawun.…”
Section: Introductionmentioning
confidence: 99%
“…Ulawun's lavas are uniformly tholeiitic basalts, with minor andesites: average SiO 2 is ∼52.75 wt% and total alkalis are <2.8 wt% [ Melson et al , 1972; Cooke et al , 1976]. Persistent SO 2 emissions from Ulawun between its eruptions have been attributed to open‐vent conditions enabled by the continued absence of any summit lava dome [ Johnson et al , 1983].…”
Section: Introductionmentioning
confidence: 99%
“…The grey region is for the forearc basalts from Reagan et al (2010); the black dashed lines are linear regression lines of data from active arc sites (Reagan et al, 2010); (d) Cr versus Y plot (after Pearce, 1982) [Colour figure can be viewed at wileyonlinelibrary.com] F I G U R E 9 (a) NiO versus Fo plot for olivines, the field for forearc peridotites is from Ishii, Robinson, Maekawa, and Fiske (1992), fields for the different mantle peridotites, ultramafic and mafic rocks are from Constantin, Hékinian, Ackermand, and Stoffers (1995). The arrow shows the fractional crystallization trend and is from Constantin (1999); (b) Cr# of spinel versus Fo content of olivine, the olivine-spinel mantle array (OSMA) given by Arai (1994), field for boninite restite from Johnson et al (1983); field for high Mg andesite restite from Tatsumi and Ishizaka (1981); boninite sample points are from Johnson et al (1983), Johnson, Jaques, Hickey, McKee, andChappell (1985), and Ramsay, Crawford, and Foden (1984); (c) Ternary Cr-Al-Fe 3+ plot for spinel after Stevens (1944), the different field are from Barnes and Roeder (2001); (d) Cr# versus Mg# plot for spinels, the field for boninites is from Dick and Bullen (1984), the fields for harzburgite, lherzolite, and metamorphic spinel is from Stevens (1944), the low greenschist metamorphism field is from Irvine (1967); (e) 100 Cr# versus TiO 2 plot of spinel, fields after Kepezhinskas, Taylor, and Tanaka (1993). Data of Songshugou ultramafic forearc (b,e) taken from Cao et al (2016) [Colour figure can be viewed at wileyonlinelibrary.com] which might be due to low-temperature reequilibration during metamorphism.…”
Section: Epidote and Plagioclasementioning
confidence: 99%